AN EVALUATION OF READING MATERIALS IN “INTERCHANGE 1 FOURTH EDITION” TEXTBOOK FOR TENTH GRADE STUDENTS IN SENIOR HIGH SCHOOL - K, Marsya Purnandhita (UICELL, 2023)
This research aims to give evaluation for Interchange I fourth edition textbook published by Cambridge in 2012 related to the investigation of good reading materials and perception of the teachers. The good reading materials criteria are employed by Patel and Jain (2008) good reading material. This research occupied a descriptive-qualitative method with a checklist and interview. The results indicated the reading material in Interchange I fourth edition is qualified as good reading materials. In addition, the results from the interview presents the perception of the teachers. Keywords: reading materials, textbooks, material evaluations